Features of uterine cavity in women with extragenital disorders and abnormal uterine bleedings - I.A. Tuchkina; L.A. Vygivska; Y.V. Blahoveshchenskyi; M.Y. Tuchkina; R.Y. Blahoveshchenskyi; D.E. Lopatenko (Publishing House TRILIST, 2022)
Objectives: to determine the features of the uterine cavity in women with extragenital disorders and abnormal uterine bleedings (AUB) using modern diagnostic methods. Materials and methods. The study involved 100 women with AUB and concomitant extragenital disorders, who constituted the main group. The control group consisted of 50 somatically healthy women. Women underwent ultrasound with Doppler mapping, and MRI if indicated to assess the condition of the pelvic organs. Due to the presence of AUB the patients of the main group underwent hysteroscopy and/or separate diagnostic curettage with further morphological assessment of the material obtained. Results. Ultrasound showed that the uterine size in women of the control group corresponded to physiological norms, and the thickness and structure corresponded to the M-echo phase of the menstrual cycle. The main group was additionally divided into subgroups depending on the detected pathological changes in the uterine cavity: endometrial polyp (glandular polyp, adenofibromatous polyp), submucous leiomatous node, endometrial polyp and submucous leiomatous node, endometrial hyperplasia, endometrial hyperplasia in combination with submucous leiomatous node. During the Doppler study the blood flow in the uterine, basal and spiral arteries was analyzed depending on the echographic assessment of the state of the uterine cavity in the main group in comparison with the data of the control group. The patients of the main group were found to have a significant increase in the level of the pulsation index in all the studied vessels in comparison with the corresponding values in the control group (Kruskal-Wallis test, Mann-Whitney test, p < 0.001). Conclusions. The most common disorder of the uterine cavity in women with extragenital diseases and AUB, detected by ultrasound scanning, were polyps of the uterine cavity and endometrial hyperplasia. A feature of blood flow in pathological processes in the uterine cavity was an increase in the pulsation index in the uterine, basal and spiral arteries in women of the main group compared to the control group.